Omnichannel Retail Strategies and Consumer Loyalty in The Hybrid Shopping Era - Anugrahwati, Anugrahwati; Asdar, Asdar; Andania, Ana; Syam, Andi Wahyuni; Nasaruddin, Nasaruddin (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
Digital transformation has fundamentally changed consumer behavior patterns and retail business strategies in Indonesia. This study aims to explore the omnichannel experiences and strategies implemented by retailers and their impact on consumer loyalty in the hybrid shopping era, with a case study in Bone Regency. Using a qualitative phenomenological approach, data was collected through in-depth interviews and participatory observation of retailers and consumers actively shopping across online and offline channels. The findings reveal that consumers are becoming increasingly flexible in their channel choices, relying on the unique advantages of each channel to achieve convenience, speed, and added value. Channel integration, information transparency, and ease of access have become basic expectations that shape consumer loyalty. Cross-channel promotional programs and integrated loyalty systems have proven to strengthen emotional attachment and encourage consumers to become brand advocates. However, the main challenges remain in synchronizing stock and promotional information, staff digital literacy limitations, and service consistency across all channels. The implications of this study underscore the importance of investing in technology, training human resources, and fostering cross-sector collaboration to create an inclusive and sustainable hybrid retail ecosystem. Recommendations are provided for businesses and policymakers to be more adaptable in responding to the dynamics of consumer behavior in the digital era